Early repolarization pattern: a marker of increased risk in patients with catecholaminergic polymorphic ventricular tachycardia - Tueluemen, Erol; Rudic, Boris; Liebe, Volker; Schimpf, Rainer; Borggrefe, Martin (Europace, 2016)
AbstractAims. The early repolarization pattern (ERP) has been shown to be associated with arrhythmias in patients with short QT syndrome, Brugada syndrome, and